The Effect of Village Fund Allocation in Improving Community Welfare (Universitas Negeri Semarang, 2022)
This study aimed to determine the effect of village fund allocation in improving community welfare in Sigotom Parratusan Village, Pangaribuan District, North Tapanuli Regency. The population in this study was the population of the village of Sigotom Parratusan totaling 1247 people. The sample in this study was 93 respondents. The sampling technique in this study used Stratified Random Sampling. The data collection technique in this study used a questionnaire arranged on a Likert scale. The analysis technique used in this research was simple regression. the coefficient of determination (R Square) was 0.623 or 62.3% the effect given by the independent variable (Village Fund Allocation) on the dependent variable (Improvement of Community Welfare) while the remaining 37, 7% was affected by other variables which included factors that affected the improvement of community welfare, the better the allocation of village funds, the higher the welfare of the community. The results of this study indicated that a good allocation of village funds had a contribution in improving the welfare of the community. This means that transparency, accountability, and participation could improve the welfare of the Sigotom Parratusan community, Pangaribuan District, North Tapanuli Regency.